2021
DOI: 10.1136/bmjopen-2021-050550
|View full text |Cite
|
Sign up to set email alerts
|

Perceived anxiety and physical activity behaviour changes during the early stages of COVID-19 restrictions in community-dwelling adults in Canada: a cross-sectional study

Abstract: ObjectivesThe COVID-19 pandemic changed daily routines, including physical activity, which could influence physical and mental health. In our study, we describe physical activity and sedentary behaviour patterns in relation to the pandemic and estimate associations between anxiety and physical activity and sedentary behaviour in community-dwelling adults.DesignCross-sectional study.SettingCalgary, Alberta, Canada.ParticipantsBetween April and June 2020, a random sample of 1124 adults (≥18 years) completed an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
1
17
0
1
Order By: Relevance
“…These results suggest that those under 80 years of age who interact with others may be more susceptible to the effects of social changes caused by the COVID-19 pandemic. Conversely, other countries have reported that positive lifestyles, such as sleep and regular mealtimes, healthy diet, cognitive stimulation, and exercise, as well as quick and straightforward provision of reliable information, can reduce anxiety among the elderly during a pandemic and have positive effects on mental health [10,12]. Thus, the results of this study indicate that measures such as raising awareness and providing information to prevent infection are incredibly significant in reducing anxiety caused by COVID-19 among older adults in their 60s and 70s who have relatively preserved activities of daily living.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These results suggest that those under 80 years of age who interact with others may be more susceptible to the effects of social changes caused by the COVID-19 pandemic. Conversely, other countries have reported that positive lifestyles, such as sleep and regular mealtimes, healthy diet, cognitive stimulation, and exercise, as well as quick and straightforward provision of reliable information, can reduce anxiety among the elderly during a pandemic and have positive effects on mental health [10,12]. Thus, the results of this study indicate that measures such as raising awareness and providing information to prevent infection are incredibly significant in reducing anxiety caused by COVID-19 among older adults in their 60s and 70s who have relatively preserved activities of daily living.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, people who experience social and emotional stressors, especially stress due to economic problems and loneliness, are more likely to have post-traumatic stress disorder (PTSD) and anxiety disorders. On the other hand, the findings in Canada [10] reported that subjects with high COVID-19 anxiety tended to be socially distant and spent more time in sedentary activities such as watching television. These findings suggest that in the spread of COVID-19 infection, a balance between physical activity promotion and mental health measures should be provided.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…One item from the IPAQ-SF measured the usual time spent sitting (ie, at work, at home, during course work, traveling by motor vehicle, and for leisure) in the last 7 days [ 39 ]. Another item captured leisure-based screen time: “In an average week, how much time per day do you usually spend watching television or other screen-based electronic devices outside your workplace (eg, video games, computer games, DVD/movies, internet, email, texting, smartphone)?” A similar item has been used previously to measure leisure-based screen time in Canadian adults [ 44 - 46 ]. We modified the item to also capture contemporary sedentary activities (eg, use of mobile technology).…”
Section: Methodsmentioning
confidence: 99%
“…The arrival of COVID-19 in Canada presents an unprecedented public health challenge, with over 2.9 million confirmed cases, 33 thousand deaths to date ( Canada, Public Health Agency, 2020 ), and a crude case fatality rate of 4.9% on April 22, 2020 ( Abdollahi et al., 2020 ), which is substantially greater than seasonal influenza death rate of approximately 0.1% ( Jordan et al., 2020 ). Although scientists have been exploring the scale, the trends and the mechanisms of this traumatic event's impact on mental health in Canada ( Bulloch et al., 2021 ; Findlay et al., 2020 ; Zajacova et al., 2020 a), the current landscape of Canadian literature on anxiety prevalence during the COVID-19 pandemic has been constrained by several methodological limitations, such as the use of non-probability sampling ( Elton-Marshall et al., 2021 ; Nwachukwu et al., 2020 ; Turna et al., 2021 ) and unvalidated measure of anxiety ( Dozois et al., 2021 ; McCormack et al., 2021 , 2020 ). While these early insights based on rapid approaches are valuable, high-quality population data on mental health needs arising from the pandemic are still needed to inform appropriate evidence-based health policies to mitigate mental health sequelae ( Pierce et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%